An engineering perspective of ceramics applied in dental reconstructions - PEREIRA, Raíssa Monteiro; RIBAS, Renata Guimarães; MONTANHEIRO, Thaís Larissa do Amaral; SCHATKOSKI, Vanessa Modelski; RODRIGUES, Karla Faquine; KITO, Letícia Terumi; KOBO, Lucas Kazunori; CAMPOS, Tiago Moreira Bastos; BONFANTE, Estevam Augusto; GIERTHMUEHLEN, Petra Christine; SPITZNAGEL, Frank Akito; THIM, Gilmar Patrocínio (Journal of applied oral science, 2023)
The demands for dental materials continue to grow, driven by the desire to reach a better performance than currently achieved by the available materials. In the dental restorative ceramic field, the structures evolved from the metal-ceramic systems to highly translucent multilayered zirconia, aiming not only for tailored mechanical properties but also for the aesthetics to mimic natural teeth. Ceramics are widely used in prosthetic dentistry due to their attractive clinical properties, including high strength, biocompatibility, chemical stability, and a good combination of optical properties. Metal-ceramics type has always been the golden standard of dental reconstruction. However, this system lacks aesthetic aspects. For this reason, efforts are made to develop materials that met both the mechanical features necessary for the safe performance of the restoration as well as the aesthetic aspects, aiming for a beautiful smile. In this field, glass and high-strength core ceramics have been highly investigated for applications in dental restoration due to their excellent combination of mechanical properties and translucency. However, since these are recent materials when compared with the metal-ceramic system, many studies are still required to guarantee the quality and longevity of these systems. Therefore, a background on available dental materials properties is a starting point to provoke a discussion on the development of potential alternatives to rehabilitate lost hard and soft tissue structures with ceramic-based tooth and implant-supported reconstructions. This review aims to bring the most recent materials research of the two major categories of ceramic restorations: ceramic-metal system and all-ceramic restorations. The practical aspects are herein presented regarding the evolution and development of materials, technologies applications, strength, color, and aesthetics. A trend was observed to use high-strength core ceramics type due to their ability to be manufactured by CAD/CAM technology. In addition, the impacts of COVID-19 on the market of dental restorative ceramics are presented.